2018
DOI: 10.5219/923
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical composition of sweet cherry (Prynus avium L.) fruit depending on the scion-stock combinations

Abstract: The results of the field and biochemical researches of sweet cherry Prunus avium L. scion Chermashnaya fruit grown on 8 clonal stocks (Kolt, Moskoviya, Izmaylovskiy, Stepnoy rodnik, AVCH-2, VSL-2, VTS-13, V-5-88) are presented. Trees productivity, the fruit average weight and the stone-fruit weight relation were studied, fruit degustation evaluation was fulfilled and the main biochemical parameters such as soluble solids, sugars sum, ascorbic acid concentration and antioxidant activity were determined. The inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…The major part of the researches in this branch of study were held by [6][7][8], who found out that photosynthesis intensity varies depending on a variety and scion-stock combination. The influence of rootstock on the quality of plum fruits is shown in the works [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The major part of the researches in this branch of study were held by [6][7][8], who found out that photosynthesis intensity varies depending on a variety and scion-stock combination. The influence of rootstock on the quality of plum fruits is shown in the works [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Многие исследователи подчеркивают роль сорта, его пластичности и стабильности (26)(27)(28) в формировании урожая в случае погодных аномалий, которые могут приводить к подмерзанию деревьев и поражению насаждений грибными болезнями (29)(30)(31). В последние годы значительное внимание уделяется селекции и использованию вегетативно размножаемых подвоев для плодовых культур как за рубежом (32)(33)(34), так и в России (35)(36)(37). Показано их влияние не только на рост и продуктивность (38,39), но и на устойчивость к болезням (40) и качество продукции (41)(42)(43).…”
unclassified